Association of wrist circumference with metabolic dysfunction associated fatty liver disease in the KADEM cohort - Al-Ajmi, Fahad; Abu-Farha, Mohamed; Albatineh, Ahmed N.; Ali, Zahraa; AL-Enezi, Abdullah; Alterki, Mohammed; Alhammad, Rashed; AlHarbi, Retaj; Shehab, Mohamed; Abdul-Ghani, Muhammad; Abubaker, Jehad; Al-Mulla, Fahd (Frontiers in Endocrinology, 2025)
IntroductionMetabolic dysfunction-associated fatty liver disease (MAFLD) is linked to metabolic dysfunction and to an increased risk of cardiovascular diseases. The early detection of individuals at high risk of MAFLD is essential for timely interventions. This study explores the association between wrist circumference and MAFLD among participants in the Kuwait Adult Diabetes and Epidemiological Multidisciplinary (KADEM) program, aiming to evaluate wrist circumference as a potential noninvasive diagnostic marker.Materials and methodsThis study included 449 participants assessed for MAFLD using FibroScan®. The MAFLD stages were classified according to the controlled attenuation parameter (CAP) score into four groups: normal (<238 dB/m), S1 (238–260 dB/m), S2 (261–290 dB/m), and S3 (>290 dB/m). Participants underwent routine clinical blood tests, and measurements of body mass index (BMI) and wrist circumference were recorded. Multiple logistic regression was used to evaluate the discriminative ability of wrist circumference and other covariates in predicting high CAP scores, with the area under the receiver operating characteristic (ROC) curve (AUC), the sensitivity, and the specificity reported.ResultsThe cohort included 184 (41.5%) normal, 77 (17.4%) S1, 81 (18.3%) S2, and 101 (22.8%) S3 participants. Wrist circumference was significantly different across groups: 16 cm for normal, 17 cm for S1 and S2, and 17.2 cm for S3 (p < 0.001). A strong correlation between wrist circumference and MAFLD was found (r = 0.328, p < 0.001). Wrist circumference was positively correlated with the triglyceride (TG), alanine transaminase (ALT), and aspartate aminotransferase (AST) levels and negatively correlated with high-density lipoprotein (HDL; p < 0.05). Adjusted analysis showed that gender, wrist circumference, ALT, and TG were significantly associated with high CAP scores. A multiple logistic regression model including these variables discriminated 76.3% of the subjects, with 69.4% sensitivity and 73.4% specificity.ConclusionWrist circumference is a potential noninvasive marker for the identification of individuals at high risk of MAFLD, representing a cost-effective screening tool for early detection. Further research is needed to confirm its clinical utility.